Alterations of DNA Methylation at GDNF Gene Promoter in the Ventral Tegmental Area of Adult Depression-Like Rats Induced by Maternal Deprivation - Zhang, Yi; Wang, Lei; Wang, Xin; Wang, Yuting; Li, Chuting; Zhu, Xiongzhao (Frontiers in Psychiatry, 2019)
Objective: To study the expression and DNA methylation of Glial cell line-derived neurotrophic factor (GDNF) gene in the development of depression-like behaviors in rats experiencing maternal deprivation stress in early life. Methods: Newborn SD rats were randomly assigned to normal control group (NOR) or maternal deprivation group (MD). Open field test (OPT), sucrose preference test (SPT), and forced swimming test (FST) were used to evaluate rats’ behaviors. Protein, mRNA, and methylation levels were measured by ELISA/Western blot, real-time PCR, and BiSulfte Amplicon sequencing PCR, respectively． Results: MD rats had significantly shorter total distance and more fecal pellets in OPT, lower sucrose preference rate in SPT, and longer immobility time in FST than NOR rats. Compared with NOR rats, MD rats showed significantly higher plasma corticosterone (CORT) level. The levels of plasma dopamine (DA) and GDNF were significantly lower in the MD rats than NOR rats. In the ventral tegmental area (VTA) tissues, MD rats had significantly higher level of methylation at GDNF gene promoter than NOR rats. The expression of GDNF mRNA and protein were significantly lower in MD rats than NOR rats. The total distance was significantly correlated with plasma DA and GDNF, DNA methylation level at GDNF promoter and GDNF mRNA level in the VTA. Fecal pellets showed a significantly correlation with plasma CORT. Sucrose preference rate was significantly correlated with plasma DA, DNA methylation level at GDNF promoter and GDNF mRNA level in the VTA. Immobility time showed a significantly correlation with plasma DA, plasma GDNF and GDNF mRNA level in the VTA. Conclusion: up-regulation of DNA methylation at GDNF gene promotor and subsequently down-regulation of GDNF gene expression in the VTA may involve in the development of depression-like behaviors in rats experiencing MD in early life.